Improving the antifouling property of polyethersulfone ultrafiltration membrane by incorporation of dextran grafted halloysite nanotubes - Yu, H.; Zhang, Y.; Sun, X.; Liu, Jian; Zhang, H. (Elsevier BV, 2014)
Polyethersulfone (PES) ultrafiltration membrane with improved antifouling property was prepared via traditional phase inversion method by incorporation of dextran grafted halloysite nanotubes (HNTs-Dextran). Fourier transforms infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and transmission electron microscopy (TEM) results showed that HNTs were modified by dextran successfully. The hybrid membranes were characterized by contact angle, scanning electron microscopy (SEM), and cross-flow filtration and antifouling measurements. The results indicated that the surface hydrophilicity of membranes was significantly improved after adding HNTs-Dextran. Compared with the pure PES membranes, the hybrid membranes possess higher flux and good antifouling properties. In addition, the content of HNTs-Dextran in the hybrid membranes was an important factor affecting the morphology and separation properties of the membranes. © 2013 Elsevier B.V.